Pregnancy history and long-term progression of cardiomyopathy in LMNA genotype-positive women. (4th February 2022) - Castrini, I; Skjolsvik, E; Estensen, M; Almaas, V; Skulstad, H; Lyssegen, E; Edvardsen, T; Lie, O; Picard, K; Lakdawala, N; Haugaa, K
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Precision Health Center for optimized cardiac care (ProCArdio), Oslo, Norway Fripro gene positive, Norwegian Research Council, Oslo, Norway Background: Competitive and non-competitive exercises have been reported to be deleterious on prognosis of LMNA genotype-positive patients. Comparable to exercise, pregnancy is a prolonged hemodynamic stress situation. Aims: We aimed to assess the association between pregnancy history and long-term progression of cardiomyopathy in women with pathogenic or likely pathogenic variants of LMNA (LMNA+). Methods: We retrospectively included consecutive LMNA+ females and recorded pregnancy data. We analyzed repeated echocardiographic examinations, including data on left ventricular (LV) end-diastolic diameter (EDD), LV ejection fraction (EF) and LV global longitudinal strain (GLS). We recorded the occurrence of atrial fibrillation (AF), atrioventricular block, sustained ventricular arrhythmias (VA), and implantation of cardiac electronic devices (ICD/CRT-D). We analysed retrospectively complications during pregnancy and peripartum period. Results: We included 89 LMNA+ women (28% probands, age 41 ± 16 years), of which 60 had history of pregnancy. Follow-up duration was 5 [IQR: 3-9] years. We analysed 452 repeated echocardiographic examinations. Women with previous pregnancy and nulliparous had a similar annual deterioration of LV EF (-0.5/year vs -0.3/year, p = 0.37, figure left panel), LV GLS (0.1/year vs 0.0/year, p = 0.35, figure right panel) and LV EDD (0.1/year vs 0.2/year, p = 0.09). Number of pregnancies was not associated with increased long-term risk of AF, atrioventricular block, sustained VA or ICD/CRT-D implantation. Pregnancy history was not associated with worse survival free from death, left ventricular assist device or need for cardiac transplantation. Arrhythmias occurred in 9% of pregnancies. No increase of maternal and fetal complications was observed. Conclusions: In our cohort of LMNA+ women, pregnancy was not associated with long-term adverse progression of cardiac dysfunction, worsening in arrhythmic progression or reduced event-free survival. Likewise, LMNA+ women generally tolerated pregnancy well, with a small proportion of patients experiencing arrhythmias.